Questions used by novice and experienced teacher in intervening mathematics class interactions - Zayyadi, Moh; Lanya, Harfin; Sulfiah, Sitti Karimah (Universitas Papua, 2023)
Learning interventions are mostly carried out by teachers in accommodating students' learning needs according to their characteristics because they can help students in improving their thinking. One form of learning intervention carried out by the teacher is through a question submission. Asking is the most common verbal communication behavior used in teaching. This research is a qualitative research with a descriptive approach because it is based on the research objective, finding out the use of questions by novice and experienced teachers in intervening mathematics class interactions. The subjects in the study were two novice teachers and two experienced teachers. The instruments used were observation sheets and interview guides which had been validated by the validator and declared feasible as research instruments. Checking the validity of the data using method triangulation and data source triangulation. The results of the study show that the use of questions by novice teachers and experienced teachers is still limited to uncovering operational knowledge and basic knowledge, not metacognitive knowledge, they are still using questions with the aim of remembering content that has been previously studied and providing calculation results and have not been able to encourage them to think critically, creatively as well as cultivating conceptual understanding and generating ideas and not directing and building student understanding so that there is a need for training to improve the quality of teachers in mastering techniques for asking questions to students in order to develop and strengthen teachers' pedagogical abilities considering the importance of teachers' pedagogical abilities in implementing the learning process and asking questions in intervening in mathematics class interactions can encourage students to think critically and creatively and foster understanding. concepts and generate ideas and can direct and build their understanding well in order to compete in a global scope.